Syntheses, Characterization and Antimicrobial Activity of Some Substituted 1,2,4-Triazole Derivatives - Singh, R.J.; Singh, D.K. (Asian Journal of Chemistry, 2010)
Syntheses of a series of 4-amino-3,5-dialkyl-1,2,4-triazoles are described. In present work, iminoester hydrochlorides (1) was treated with acyl hydrazines to obtain acylhydrazones (2). The compound acylhydrazones (2) converted to the 4-amino-3,5-dialkyl-1,2,4-triazoles (3) in good yields by treatment with hydrazine hydrate. The newly compounds were characterized by spectral and elemental analyses. Some compounds were screened for their antibacterial activity against S. aureus, E. coli, B. subtilis and P. aeruginosa. All compounds carring 1,2,4-triazole moiety showed significant antimicrobial activity.